Enhanced biomethane production by co-digestion of mixed sewage sludge and dephenolised two-phase olive pomace. Issue 5 (May 2022) - Fragoso, Rita; Henriques, Ana Catarina; Ochando-Pulido, Javier; Smozinski, Nicole; Duarte, Elizabeth
In this study, co-digestion of mixed sewage sludge from a wastewater treatment plant (WWTP) and partially dephenolised two-phase olive pomace (DOP) as a co-substrate was addressed with the aim of improving the biodigestibility of both substrates. The introduction of DOP into WWTP anaerobic digester facilities could significantly increase biomethane production and enhance the sustainability of both activities. An improvement in the system's performance was supported by stability parameters: total alkalinity increased and stabilised with the addition of 5% v/v DOP, and the specific energy loading rate was maintained at 0.177 ± 0.03 d −1, which indicated better buffer capacity and stability in the bioreactor, and the possibility of enhancing the organic loading rate. In terms of average daily biogas production rate, an increase of 39% was achieved, up to 0.39 ± 0.11 L L −1 d −1 . Moreover, there was a 40% and 37% improvement in specific methane production and methane production rate, respectively, up to 0.28 ± 0.02 L CH4 gTVS −1 and 0.26 ± 0.08 L L −1 d −1 . In addition, the proposed strategy leads to an energy saving of 20, 328.6 kWh year −1 at the WWTP as a result of the electric energy production surplus, corresponding to an annual saving of €3293.23.